KRITIK TERHADAP PSAK PERBANKAN SYARIAH IAI DAN AAOIFI - Sofyan Syafri Harahap (Media Riset Akuntansi, Auditing & Informasi, 2001)
The Conceptual framework for presentation of financial statement of Islamic bank and Accounting standards for Islamic banking have been formulated by Indonesian Asso-ciation of Accountants (cooperated with Bank Indonesia, Indonesia central bank.. The standards are called PSAK (Pemyataan Standard Akuntansi Keuangan). The frame-work and the standards, mainly, has refered to the MOIFI standard for Islamic bank-ing. This paper discusses the the content of the those two promulgations (MOIFI and PSAK) and also criticizes the lack of lawhid" concept in those two. The author argues that those two standards still based on the conventional accounting philosophy in which the capitalist interest is mainly the focus of the information disclosure.Keywords: Islamic accounting, accounting standard, Islamic banking, Indonesian accounting standard (PSAK)